Validitas Konten Video Pembelajaran Matematika Berbasis Digital Storytelling Topik Data dan Ketidakpastian - Shubhiy, Annisa Nadiya Fauziyah; Masriyah, Masriyah; Sari, Yurizka Melia (MATHEdunesa, 2025)
Mathematics learning videos are audio visual media that make lessons more engaging by aligning with students’ audio-visual learning styles and illustrating real-life applications through digital storytelling. However, numeracy performance remains low—only 19% (4 of 21 students) mastered topics like mean, median, mode, and range. Efforts to address this problem are to use mathematics learning videos based on digital storytelling to strengthen students’ numeracy. This study aims to describe the content validity making such a video for strengthening students’ numeracy skills. In this research used the ADDIE development model, which focuses on three stages: Analyze, Design, and Develop with evaluations at each stage. However, this article focuses on the validation assessment of mathematics learning videos based on digital storytelling. The instruments used consist of a material expert validation instrument and a learning video validation instrument. The media was validated by three experts in the field of learning media, visual programming, and digital storytelling. The data analysis technique uses the Aiken V formula. Based on this, the results of the validation analysis are shown by obtaining a score of 0.854 from video experts (highest in usefulness) and 0.83 from material experts (highest in learning objectives) both were categorized as valid. The assessment by experts shows that the mathematics learning video is suitable for use with revisions. Several revisions were made to mathematics learning video based on digital storytelling to make it more interesting. Further research is recommended to develop the mathematics learning video into an application that can be used offline and allows for automatic answer storage settings.